Drug Repurposing - Advances, Scopes and Opportunities in Drug Discovery 2023
DOI: 10.5772/intechopen.108729
|View full text |Cite
|
Sign up to set email alerts
|

Development of Phytomedicines as Novel Antimalarial Lead Molecules: Progress towards Successful Antimalarial Drug Discovery

Abstract: Among numerous life-threatening infectious diseases (HIV/AIDS, TB, NTDs and EIDs), malaria continues to be the deadliest parasitic disease caused by Plasmodium protozoa transmitted by an infective female Anopheles mosquito. Plasmodium falciparum, the potentially fatal malaria parasite, is believed to be responsible for most of the morbidities and mortalities associated with malaria infections. Artemisinin-based Combination Therapies (ACTs) are currently considered to be the frontline therapy against malaria ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Despite the global healthcare importance of leishmaniasis and malaria, there are only a few drugs often deployed to treat them in the clinical setting. Ironically, multiple reports revealed that the efficacy of the existing antileishmanial and antimalarial drugs is often conceded due to suboptimal treatment outcomes and the advent of drug-resistant Plasmodium falciparum [ 5 11 ] which is responsible for most of the mortality and morbidity associated with malaria [ 12 14 ]. Thus, the discovery of new antileishmanial and antimalarial agents with desirable therapeutic efficacy and tolerable side effects is highly demanded to treat infections caused by leishmaniasis and malaria [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the global healthcare importance of leishmaniasis and malaria, there are only a few drugs often deployed to treat them in the clinical setting. Ironically, multiple reports revealed that the efficacy of the existing antileishmanial and antimalarial drugs is often conceded due to suboptimal treatment outcomes and the advent of drug-resistant Plasmodium falciparum [ 5 11 ] which is responsible for most of the mortality and morbidity associated with malaria [ 12 14 ]. Thus, the discovery of new antileishmanial and antimalarial agents with desirable therapeutic efficacy and tolerable side effects is highly demanded to treat infections caused by leishmaniasis and malaria [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%